The Relationship Between Depth of Vocabulary Knowledge, Home Literacy, and English Reading Comprehension Achievement (A Case of The First-Year Mechanical Engineering Department Students of Diponegoro University) - Nuriska Denhas, Kiki; Linggar Bharati, Dwi Anggani (Universitas Negeri Semarang, 2017)
This study aimed at describing the correlation and contribution between learners’ depth of vocabulary, home literacy, and English reading comprehension achievement. This study was significant due to the lack of empirical research conducted in this topic in Indonesian context. The participants in this study were first-year Mechanical Engineering Department EFL learners at Diponegoro University, Central Java, Indonesia (n=77). The data were gathered by using Word Association Test (WAT), Home Literacy Questionnaire (HLQ), and Reading Comprehension Test (RCT). The findings revealed that: (1) learners’ depth of vocabulary knowledge significantly correlated to English reading comprehension achievement (r=0.662), (2) learners’ depth of vocabulary knowledge contributed 43.9% to their English reading comprehension achievement, (3) learners’ home literacy significantly correlated to English reading comprehension achievement (r=0.610), (4) learners’ home literacy accounted for 37.3% to their English reading comprehension achievement, (5) learners’ depth of vocabulary knowledge and home literacy significantly correlated to their English reading comprehension achievement (r=0.749), and (6) learners’ depth of vocabulary knowledge and home literacy contributed 56.1% to their English reading comprehension achievement. The findings added the body of literature that the higher the adult EFL learners’ score on depth of vocabulary knowledge and home literacy, the higher their score on English reading comprehension achievement.